Analysis of Needs Planning, Realization and Optimization of Health Human Resources at the UPT of Public Health Center, Blitar District - Sunarsih Sunarsih (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The crucial problem of Health Human Resources currently facing is the number, distribution, and quality of health workers. Therefore, it is necessary to take concrete steps in addressing the challenges of this problem by meeting the availability of quality Health Human Resources according to needs, distributed fairly and evenly, and utilized efficiently and effectively. The focus of this research is how the planning of needs, realization and optimization of health human resources at the UPT Puskesmas in Blitar district. This type of research is quantitative qualitative with a case study approach. The results of this study illustrate that in running the public health center program still varies Adequacy of availability of health human resources that are less than ideal, both strategic and non-medical personnel. The planning mechanism for health human resource needs is carried out periodically once a year and used as a proposal report to the Health Office. Development planning still has obstacles due to lack of understanding of the manager program and there is no standard format yet. As an effort to optimize health human resources at the UPT Puskesmas, efforts were made to maximize the existing health human resources by giving multiple assignments and several strategies carried out by the head of the UPT Puskesmas in Blitar district. The realization of the planning for calculating the need for health Human Resources made annually from the UPT Puskesmas as a report to the Health Office has been realized, although not yet fully.